Transforming the functional equation of Gołąb-Schinzel into one of Cauchy - Kahlig, Peter; Schwaiger, Jens (Annales Mathematicae Silesianae, 1994)
It is shown that Gołąb-Schinzel's equation may be transformed into one of Cauchy's equations by an embedding and limit process concerning the general continuous solution.